Promoting Critical Thinking and Public Speaking Skills Through Debates at Tridinanti University - Setiawan, Heru; Budiyanto, Darmawan; Jamilul Insan (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2024)
Critical thinking and public speaking skills are common issues now in Indonesia, but not many high school students have good critical thinking and public speaking skills in English. Therefore, this study was aimed to find out whether or not there was any significant differences in speaking skill between students who were taught by using debate technique and those who were not. There were 16 students of the third semester students involved in this study as the sample. They were divided into two groups, experimental group consisted of 8 students and control group consisted of 8 students. This study used quasi nonequivalent group design. The experimental group were taught by using debate technique meanwhile the control group were taught by using lecturing method. The result showed that the mean score of experimental groups increased from 63.28 in pretest to 73.80 in posttest. Furthermore, the result of independent t-test from experimental and control group shown that the t-obtained was 10.942 and it was higher than t-table 2.0049. It meant that there were any significant differences between experimental and control groups which was caused by debate technique given to the experimental group. It can be concluded that there was any significant difference between students who were taught using debate and students who were not. The results show that using debating activities played a significant role in improving and enhancing the critical thinking ability of high school students. Students’ feedback concerning the use of debating activities are, in general, also quite optimistic. Besides, the research proposes some suggestions for minimizing the drawbacks of using debating activities to enhance the potentiality of this method and make it more interesting, meaningful and effective.